2023
DOI: 10.3390/diagnostics13071289
|View full text |Cite
|
Sign up to set email alerts
|

Deep-Learning-Enabled Computer-Aided Diagnosis in the Classification of Pancreatic Cystic Lesions on Confocal Laser Endomicroscopy

Abstract: Accurate classification of pancreatic cystic lesions (PCLs) is important to facilitate proper treatment and to improve patient outcomes. We utilized the convolutional neural network (CNN) of VGG19 to develop a computer-aided diagnosis (CAD) system in the classification of subtypes of PCLs in endoscopic ultrasound-guided needle-based confocal laser endomicroscopy (nCLE). From a retrospectively collected 22,424 nCLE video frames (50 videos) as the training/validation set and 11,047 nCLE video frames (18 videos) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…They achieved high diagnostic accuracy for both CLE-based and histopathologic diagnosis of esophageal dysplasia and its precursors, similar to human accuracy [30]. Lee et al also advocate the use of deep learning models in evaluation of pancreatic cystic lesions (PCL) by CLE [31]. Aubreville et al presented a significantly improved overall performance of 94,8% using a model for deep learning-based detection of motion artifacts in CLE images [32].…”
Section: Cle In Head and Neck Surgerymentioning
confidence: 78%
“…They achieved high diagnostic accuracy for both CLE-based and histopathologic diagnosis of esophageal dysplasia and its precursors, similar to human accuracy [30]. Lee et al also advocate the use of deep learning models in evaluation of pancreatic cystic lesions (PCL) by CLE [31]. Aubreville et al presented a significantly improved overall performance of 94,8% using a model for deep learning-based detection of motion artifacts in CLE images [32].…”
Section: Cle In Head and Neck Surgerymentioning
confidence: 78%
“…Additionally, there is a lack of studies that perform external validation of the AI models used in the EUS of the pancreas. In the absence of external validation, there is a lack of assurance regarding the model’s generalizability, which may result in the possibility of overestimating the outcomes 27 , 28 , 40 . Efforts are underway to develop techniques and methods that enhance the reliability and interpretability of AI models, allowing technicians and clinicians to understand and trust the results generated by AI algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the development of computer technology and artificial intelligence has facilitated the application of radiomics and deep learning methods in the classification of pancreatic cystic tumors, [6][7][8][9] which provide a basis for detection and diagnosis in the clinic. Xie et al 10 extracted radiomics features based on CT images and demonstrated that the radiomics model had good performance in preoperative identification of MCN and SCN.…”
Section: Introductionmentioning
confidence: 99%